Stability Analysis of Selected Jute (Corchorus capsularis L.) Genotypes in Saline and Non-saline Soils of Bangladesh (The Agriculturists, 2016)
Ten white jute genotypes (Corchorus capsularis L.) were evaluated across three different locations including saline and non-saline soils of Bangladesh during 2014 to assess genotype × environment interaction and stability for plant height, base diameter, fresh weight with leaves, dry stick weight and dry fiber weight. Additive Main Effect Multiplicative Interaction (AMMI) model was used to assess the additive and multiplicative interaction of jute genotypes for these characters across three environments. Significant variations in genotype environment interaction were observed for all characters except plant height and base diameter. Based on stability parameters bi1 and bio, the genotype C-3465 showed stability for plant height, D-154 for base diameter and fresh weight with leaves. The genotypes C-2753 showed stability for fresh weight with leaves, without leaves and dry stick weight, CVL-1 for fresh weight without leaves, C-2760 for fresh weight with leaves, without leaves and for dry fiber weight across saline and non- saline area. Heritability in broad sense was quite high for all characters (85-90%) except plant height (17%) indicating less environmental fluctuation. Expected genetic advanced of mean was moderate to high (14%-29.16%) except plant height (3.20%) indicating the good scope of selection for improving the traits.The Agriculturists 2015; 13(2) 25-35